Biogeographic history and high-elevation adaptations inferred from the mitochondrial genome of Glyptosternoid fishes (Sisoridae, Siluriformes) from the southeastern Tibetan Plateau. (December 2015) - Ma, Xiuhui; Kang, Jingliang; Chen, Weitao; Zhou, Chuanjiang; He, Shunping
Abstract Background The distribution of the Chinese Glyptosternoid catfish is limited to the rivers of the Tibetan Plateau and peripheral regions, especially the drainage areas of southeastern Tibet. Therefore, Glyptosternoid fishes are ideal for reconstructing the geological history of the southeastern Tibet drainage patterns and mitochondrial genetic adaptions to high elevations. Results Our phylogenetic results support the monophyly of the Sisoridae and the Glyptosternoid fishes. The reconstructed ancestral geographical distribution suggests that the ancestral Glyptosternoids was widely distributed throughout the Brahmaputra drainage in the eastern Himalayas and Tibetan area during the Late Miocene (c. 5.5 Ma). We found that the Glyptosternoid fishes lineage had a higher ratio of nonsynonymous to synonymous substitutions than those found in non-Glyptosternoids. In addition, ωpss was estimated to be 10.73, which is significantly higher than 1 (p -value 0.0002), in COX1, which indicates positive selection in the common ancestral branch of Glyptosternoid fishes in China. We also found other signatures of positive selection in the branch of specialized species. These results imply mitochondrial genetic adaptation to high elevations in the Glyptosternoids. Conclusions We reconstructed a possible scenario for the southeastern Tibetan drainage patterns based on the adaptive geographical distribution of the Chinese Glyptosternoids in this drainage. The Glyptosternoids may have experienced accelerated evolutionary rates in mitochondrial genes that were driven by positive selection to better adapt to the high-elevation environment of the Tibetan Plateau.